Language Shift and Maintenance: The Case of Algerian Immigrants in France - MEDJEDOUB, Rima (Milev Journal of Research and Studies, 2015)
The focus of the present study is on language choice among Arabic/French bilinguals in the Algerian immigrant community in France. Such a choice reflects the status of Arabic maintenance/shift as a minority language in France. This research aims to answer the question: In the case of Algerian immigrants in France, does Arabic undergo a language shift or maintenance? Why? In order to end up with illuminating results, an email questionnaire was conducted with 20 Algerian immigrants in France. The findings indicate that Arabic is lost starting from the third generation. Even though this small-scale investigation has its inadequacies, it throws light on some causes behind the decay of Arabic in the host country. Once reasons are known, remedial measures can be identified and taken. Besides, one of the important results is that our immigrants share positive attitudes towards their mother tongue which can be relied on as a strong maintenance factor eventually.